1997
DOI: 10.1152/jn.1997.77.3.1606
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and Response Characteristics of Human Olfactory Neurons

Abstract: Transduction mechanisms were investigated in human olfactory neurons by determining characteristics of odorant-induced changes in intracellular calcium concentration ([Ca2+]i). Olfactory neurons were freshly isolated from nasal biopsies, allowed to attach to coverslips, and loaded with the calcium-sensitive indicator fura-2. Changes in [Ca2+]i were studied in response to exposure to individual odors, or odorant mixtures composed to distinguish between transduction pathways mediated by adenosine 3'5'-monophosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
67
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 32 publications
12
67
0
Order By: Relevance
“…However, anatomical studies (Féron et al, 1998;Nibu et al, 1999) have shown that ORNs (identified by expression of olfactory marker protein, a molecular marker unique to mature ORNs) can be found as far down as the superior aspect of the medial turbinate, although there is considerable individual variability. These findings are supported by studies where biopsies from the high middle turbinate and apposed septum have yielded functional ORNs (Rawson et al, 1997;Thü raü f et al, 1996) or viable explant cultures of olfactory neurons (Féron et al, 1998, Gomez et al, 2000b.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, anatomical studies (Féron et al, 1998;Nibu et al, 1999) have shown that ORNs (identified by expression of olfactory marker protein, a molecular marker unique to mature ORNs) can be found as far down as the superior aspect of the medial turbinate, although there is considerable individual variability. These findings are supported by studies where biopsies from the high middle turbinate and apposed septum have yielded functional ORNs (Rawson et al, 1997;Thü raü f et al, 1996) or viable explant cultures of olfactory neurons (Féron et al, 1998, Gomez et al, 2000b.…”
Section: Introductionmentioning
confidence: 57%
“…Human ORNs have a resting [Ca 2ϩ ] i level of about 50 to 70 nM (Gomez et al, 2000a;Rawson et al, 1997). When stimulated with either of these two odorant mixes, about 30% of the cells tested (n ϭ 322) responded with a change in [Ca 2ϩ ] i .…”
Section: Stimulus-elicited Calcium Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only one group has successfully imaged Ca 2+ influx in individual cilia [20,21], although many have recorded odor-induced Ca 2+ changes in dendrites and soma of ORNs [22][23][24][25][26][27][28][29]. The fact that in most odor responses, the Ca 2+ signal is propagated from the cilia to the soma suggests that (1) voltage-gated Ca 2+ channels and/or the Ca 2+ -induced Ca 2+ release machinery (Ca 2+ -sensitive stores) must be present to move the signal to the soma, and (2) the propagated Ca 2+ signal is bringing odor-specific information to the soma.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory receptors are broadly selective (Katada S et al, 2005), albeit species differences have been reported (Rawson NE et al, 1997), and respond together in a combinatorial way (Rennaker RL et al, 2007;Zou Z, Buck LB, 2006). It is, then, important to complement experiments that use molecular, cellular, and tissue approaches with those that use systemintegrated behavioral approaches.…”
Section: Introductionmentioning
confidence: 99%